2018
DOI: 10.7759/cureus.2019
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired Pneumonia with Methicillin-resistant Staphylococcus Aureus in a Patient Admitted to the Intensive Care Unit: A Therapeutic Challenge

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) was previously considered a purely nosocomial pathogen. However, community-acquired MRSA has recently emerged as an important cause of severe necrotizing community-acquired pneumonia (CA-MRSA) in previously healthy individuals. This new pathogen exhibits antibiotic resistance and is linked to extended hospital stay and higher mortality. CA-MRSA has presented new therapeutic challenges due to high vancomycin treatment failure and lack of specificity of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
7
0
1
Order By: Relevance
“…is indicates that MRSA is becoming an important pneumonia-causing pathogen in the study area and supported by other studies [12,53,54].…”
Section: Discussionsupporting
confidence: 84%
“…is indicates that MRSA is becoming an important pneumonia-causing pathogen in the study area and supported by other studies [12,53,54].…”
Section: Discussionsupporting
confidence: 84%
“…have previously been implicated in nosocomial cases although a recent report revealed community-acquired -MRS pneumonia, particularly CA-MRSA. 47 The low resistance of Staphylococcus species to GEN and CIP in this study indicated that these could be a useful alternative for treatment in cases where first-line antibiotics represent a failure. An Ethiopian study reported similar findings.…”
Section: Discussionmentioning
confidence: 68%
“…4 Lethality of MRSA CAP is believed to originate from Panton-Valentin-Leukocidin (PVL) toxin produced by MRSA causing leukocytes death and subsequently significant lung necrosis and lethal pneumonia. [3][4][5] In a study by Bhatta et al reported PVL-positive in 90.4 % of community -acquired MRSA, whereas only 7.1% of hospital-acquired MRSA were PVL-positive, suggesting that PVL may be a marker of community-acquired MRSA. 6 The incidence of MRSA CAP is undetermined yet.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 However, linezolid has been favorably suggested as a better alternative to vancomycin as it has a better lung penetration, with almost 100% oral bioavailability, and does not need dose adjustment or frequent level monitoring comparing to vancomycin. 3,4 Several studies recommended a rapid test for early identification of MRSA to avoid the overuse of anti-MRSA antibiotics which may lead to antibiotics resistance, increased cost, and clostridium difficile infections. 9 We herein report an uncommon case of severe MRSA CAP who presented with altered mental status and septic shock in a previously healthy old male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation